Therapeutic Architecture as a Design Approach for Cancer Community Center - Arsyandy, Adella Nusyabila; Ratnasari, Anisza (Lakar: Jurnal Arsitektur, 2025)
In Indonesia, the prevalence of cancer is one of the deadliest diseases in the world, increasing significantly every year. Various treatment methods are currently available, but they are very physically and mentally draining for patients. Therapeutic architecture offers a holistic approach to the care and recovery of cancer patients by creating an environment that supports physical, psychological, and social health. The main concepts of therapeutic architecture are care in community, design for domesticity, social valorization and integrated with nature. This study aims to explore the implementation of therapeutic architecture principles as a pre-design concept for a cancer community center. This topic focuses on the application of architectural design principles that support the healing process of cancer patients through a specially designed physical environment. This study is important because it identifies how architectural elements such as natural lighting, green open spaces, and spatial designs that support social interaction can affect the physical and psychological well-being of patients. This approach provides new insights into creating facilities that not only fulfill medical functions, but also accelerate recovery by creating a calming and supportive environment for therapy. The methods used are literature studies and interpretive analysis to interpret the implementation of therapeutic architecture into design strategies. The results of the study indicate that the design of space and built environment that pays attention to humans, space and user activities by integrating natural elements, social space, and a comfortable and warm atmosphere can provide a positive impact and provide an optimal healing environment.